2020
DOI: 10.4269/ajtmh.20-0280
|View full text |Cite
|
Sign up to set email alerts
|

Point-of-Care Lung Ultrasound Findings in Patients with COVID-19 Pneumonia

Abstract: Patients with novel coronavirus disease typically present with bilateral multilobar ground-glass opacification with a peripheral distribution. The utility of point-of-care ultrasound has been suggested, but detailed descriptions of lung ultrasound findings are not available. We evaluated lung ultrasound findings in 10 patients admitted to the internal medicine ward with COVID-19. All of the patients had characteristic glass rockets with or without the Birolleau variant (white lung). Thick irregular pleural li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
106
0
6

Year Published

2020
2020
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 82 publications
(119 citation statements)
references
References 16 publications
6
106
0
6
Order By: Relevance
“…Nevertheless, it should be considered that the speci city and the positive predictive of the same LUS signs may be lowered in a normal setting of non epidemic COVID-19. Indeed, the sonographic ndings described in our case series and in the current available literature on this topic 11,12,13,14,15 shows a considerable overlap with many other lung diseases. An irregular pleural line with increased B-lines may be visible in ARDS, heart failure, nephrotic syndrome, bacterial pneumonia, other viral pneumonia, also minimal pleural effusion, hydropneumothorax, brosis, pulmonary contusion, exacerbations of chronic obstructive pulmonary diseases and neoplastic lymphangitis 16 .…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Nevertheless, it should be considered that the speci city and the positive predictive of the same LUS signs may be lowered in a normal setting of non epidemic COVID-19. Indeed, the sonographic ndings described in our case series and in the current available literature on this topic 11,12,13,14,15 shows a considerable overlap with many other lung diseases. An irregular pleural line with increased B-lines may be visible in ARDS, heart failure, nephrotic syndrome, bacterial pneumonia, other viral pneumonia, also minimal pleural effusion, hydropneumothorax, brosis, pulmonary contusion, exacerbations of chronic obstructive pulmonary diseases and neoplastic lymphangitis 16 .…”
Section: Discussionsupporting
confidence: 51%
“…Frequently reported LUS ndings are the appearance of multiple, con uent or not, B-lines, a thickened and irregular pleural line and small super cial or large areas of consolidation 11,12,13 . Also minimal or rarely larger pleural space uid effusions has been evidenced 14,15 .…”
Section: Introductionmentioning
confidence: 99%
“…LUS has several advantages, including the lack of radiation exposure, the possibility of multiple repetitions, the reduction of exposure of healthcare professionals to SARS-CoV-2 and the mitigation of the shortage of personal protective equipment. 6 Furthermore, LUS also shows prognostic abilities in acute respiratory distress syndrome (ARDS) before hypoxemia becomes evident. 5 In fact, in the T A B L E 1 Distribution of the number of affected areas, consolidation, and other findings of lung ultrasound in the sample evaluated In the present study, we observed that half of the patients had unilateral lung damage, unlike a systematic review of thoracic CT scans in patients with COVID-19 who observed bilateral lung involvement in 87% of cases and multilobar involvement in 78.8% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…The ultrasound exams were performed in six areas of each hemithorax (two anterior, two lateral and two posterior) while the patients were seated. 6 The transducer was covered with a probe cover, and the ultrasound device was cleaned with disinfectant wipes after each use. LUS images were examined for the following signs: B-lines >2, coalescent B-lines, consolidations, pleural effusion and pleural thickening.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation